Age-related macular degeneration and risk of total and cause-specific mortality over 15 years. (February 2016) - Gopinath, Bamini; Liew, Gerald; Burlutsky, George; Mitchell, Paul
Highlights: The link between AMD and long-term mortality risk is not established. Late AMD predicted an increased risk of 15-year total mortality in men. Late AMD independently predicted stroke mortality in women, 15 years later. These findings indicate that late AMD is a likely marker of biological aging. Abstract: Objective: We aimed to investigate the independent association between AMD and risk of ischemic heart disease (IHD), stroke, and cardiovascular (CVD) mortality, and all-cause mortality over 15 years. Methods: 3654 participants aged 49+ years at baseline were followed over 15 years. AMD was assessed from retinal photographs. Deaths and cause of death were confirmed by data linkage with the Australian National Death Index. Hazard ratios (HRs) and 95% confidence intervals (CIs) were assessed using Cox models. Results: 71.4% ( n  = 162) and 34.6% ( n  = 1037) of participants with any AMD and no AMD, respectively, died over 15 years. After multivariable-adjustment, no significant associations were observed between AMD and total- and cause-specific mortality in the overall cohort. However, among men, late AMD at baseline was associated with an increased risk of all-cause mortality ( n  = 22; 95.7%), 15 years later: multivariable-adjusted HR, 1.80 (95% CI 1.04–3.11). Women with late AMD had 2-fold increased risk of stroke mortality ( n  = 15; 28.9%), HR 2.10 (95% CI 1.08–4.06). Early-stage AMD was not associated with mortality risk. Conclusion: Late AMD independently predicted all-cause mortality in men and stroke mortality in women, over 15 years. Although underlying mechanisms are unclear, these findings indicate that late AMD is a marker of biological aging.